Climate Change and Socio-Ecological Transformation Vulnerability and Sustainability - Malakar, Kousik Das.; Kumar, Manish; Anand, Subhash; Kuzur, Gloria (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on various psycho-social and socio-physical aspects of climate change and includes a wide range of case studies. Included topics are notable climate-related social thinking; climate vulnerability; transformation in socio-ecological subsystems; bioclimatological, urban bioclimatological and socio-bioclimatic ideas; disasters; policy instruments; climate justice; human rights; and sustainability. The book distinguishes itself from similar works by including a wide variety of topics and assists policy management in the current and upcoming climate crisis era. This book also addresses the Sustainable Development Goals 13 (Take Urgent Action to Combat Climate Change and Its Impacts), highlighting resilience, recovery potential and adaptive capacity, climate change measures integrated into policies and planning, and knowledge and capacity to mitigate climate change. The ideas covered in this book evolved in response to the current climate crisis, ideas that the authors believe will aid in societal management and development in the present and future. The book is a useful source for planners, geographers, professionals, academics, government officials, laypeople, and others interested in climate change.
Introduction -- Climate, Climate Change Ecology and Socio-ecological Environments.-Dimensions of the Socio-ecological Subsystems -- Climate Vulnerability and Socio-ecological Transformation -- Bioclimatology and Urban Bioclimatology -- Disaster, Policy Instruments, and Sustainability -- Climate Change and Socio-Ecological Transformation -- Climate Change, Justice, and Rights -- Climate Crisis and Socio-ecological Sustainability.
Keywords: Climatology; Bioclimatology; Sociology; Sustainability; Climate Sciences; Climate Change Ecology; Sociology; Sustainability